2022
DOI: 10.1099/jmm.0.001501
|View full text |Cite
|
Sign up to set email alerts
|

Hospital sink traps as a potential source of the emerging multidrug-resistant pathogen Cupriavidus pauculus: characterization and draft genome sequence of strain MF1

Abstract: Introduction. Cupriavidus pauculus is historically found in soil and water but has more recently been reported to cause human infection and death. Hospital sink traps can serve as a niche for bacterial persistence and a platform for horizontal gene transfer, with evidence of dissemination of pathogens in hospital plumbing systems driving nosocomial infection. Gap Statemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 101 publications
(147 reference statements)
2
2
0
Order By: Relevance
“…12 The MALDI-TOF MS, nanopore, 16S rRNA and next generation sequencing (NGS) technologies allows rapid and accurate detection of bacterial pathogens. 13 The isolate identified in the present case was multidrug resistant and showed resistance to various group of antibiotics including imipenem, amikacin, gentamicin, and tobramycin which appears to be in concordance with previous studies. The optimal therapeutic regimen for treating infections caused by C. pauculus remains unclear because of the limited data.…”
Section: Discussionsupporting
confidence: 92%
“…12 The MALDI-TOF MS, nanopore, 16S rRNA and next generation sequencing (NGS) technologies allows rapid and accurate detection of bacterial pathogens. 13 The isolate identified in the present case was multidrug resistant and showed resistance to various group of antibiotics including imipenem, amikacin, gentamicin, and tobramycin which appears to be in concordance with previous studies. The optimal therapeutic regimen for treating infections caused by C. pauculus remains unclear because of the limited data.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that, Cupriavidus paucula had three heavy metals genes nccA, pbrA, and czcD. Butler et al (2022), also demonstrated that Cupriavidus paucula had many heavy metals resistance genes as cnrR, cnrY, czcA-D, czcI, czcN, and nikR that code for resistance to nickel, cobalt, cadmium and zinc.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, 2,5-Furandicarboxylic acid is a microbial metabolite, a product of the oxidation of hydroxymethylfurfural (HMF) by the enzyme furfural/HMF oxidoreductase, which is found in the Gram-negative environmental bacterium Cupriavidus basilensis (family Burkholderiaceae). Dissemination of these environmental pathogens in hospital plumbing systems has been reported, driving nosocomial infection [ 65 ], and clinical isolates have been collected and sequenced. Moreover, 2,5-Furandicarboxylic acid increases with the level of fructose consumed [ 66 ].…”
Section: Discussionmentioning
confidence: 99%